A model of factors influencing safety behaviour and awareness among Vietnamese construction workers - Duy Khanh Ha (Vietnam Journal of Science, Technology and Engineering)
Ensuring labour safety remains a critical concern within the construction industry, particularly in Vietnam, where workers face various challenges related to awareness and behaviour. This study explores the factors influencing workers’ safety behaviour and perception. Key factors were identified through a review of existing literature and consultations with experts. Data were collected via questionnaires distributed to three respondent groups, differentiated by job roles, project stakeholders, and years of experience. The data were analysed using appropriate statistical methods. The findings reveal 23 factors, categorised into three groups: worker characteristics, management capacity, and working conditions. The study found no significant differences in the assessment of these factors’ effects on worker safety behaviour across the respondent groups. Using exploratory factor analysis (EFA), these initial factors were consolidated into principal groups, accounting for over 60% of the total variance. Practically, the study provides insights into the content and implications of each factor and group. These findings can assist safety managers in better understanding worker behaviour and attitudes, thereby facilitating the development of appropriate policies.